Program of Reading Activities for Surah Al-Hadid Verses 1-3 and Surah Al-Hasyr Verses 22-24 Ba'da Subuh (Study of Living Qur'an Among Niha'ie IDIA Prenduan Students) - Nisrina Audini; Agus Kharir (Classroom: Journal of Islamic Education, 2025)
The activity of reading selected surahs has existed or started in the Rusunawa building which is occupied by final semester students, reading the Al-Qur'an in several selected surahs (surah al-Hadid verses 1-3 and surah al-Hasyr verses 22-24), this is a routine activity carried out after the morning congregational prayer which is led directly by the chaplain of the private department. In this research we will analyze the activities carried out by IDIA Prenduan niha'ie students every day, it is hoped that a deeper understanding can be found. regarding these routine activities and looking for their uniqueness, benefits and implications in everyday life. The problem raised in this research is the motives, aims and benefits of reading surah al-Hadid verses 1-3 and surah al-Hasyr verses 22-24 among Niha'ie IDIA Prenduan students. This research uses a descriptive qualitative approach with a phenomenological type of research. The data collection techniques used in this research are observation, interviews and documentation. This research resulted in 1. The aim of the program for reading surah al-Hadid verses 1-3 and surah al-Hasyr verses 22-24 ba'da Fajr at Niha'ie Putri IDIA Prenduan, firstly, is to familiarize students with reading surahs al-Hadid verses 1-3 and surah al-Hashr verses 22-24 after dawn so that you can wake up and get peace of mind so you can avoid unwanted bad things. 2. The benefits obtained by female students are that students receive personal protection, eliminate feelings of worry, fear, and calm their hearts.